"Starting where the children are": A process evaluation of the mother tongue-based multilingual education implementation - Jennifer D. Monje; Aniceto C. Orbeta; Kris A. Francisco-Abrigo; Erlinda M. Capones (Philippine Institute for Development Studies (PIDS), 2019)
The primary rationale of the Mother Tongue-Based Multilingual Education (MTB-MLE) program is to begin where the children are, which means building up on what children already know. It is designed to implement a learner-centered education from the beginning of the education ladder. The MTB-MLE policy may be said to be in its infancy in terms of official implementation, but it has had a long and unrecognized history in Philippine education. Implemented along the margins of dominant language-in-education policies as "auxiliary" medium of instruction (MOI) from the turn of the century until recently, the mother tongue (MT) became primary MOI and official Department of Education (DepEd) language-ineducation policy in 2009 via Department Order (DO) No. 74. This process evaluation (PE) sought to determine how the program is proceeding since the passage of RA 10533 or the Enhanced Basic Education Act of 2013. It specifically looked at program theory, service delivery and utilization, and program organization. To capture the breadth of conceptual and implementation issues, eighteen (18) randomly selected elementary schools were visited from among private and public school systems, distributed according to DepEd's typology of small, medium, and large schools; island groupings of Luzon, Visayas and Mindanao; and from both linguistically diverse contexts (LDCs) and less linguistically diverse communities (L-LDCs). Key informant interviews (KIIs) with former and current DepEd officials at the national, regional, and division levels, and focus group discussions (FGDs) with teachers and parents, were done. An online survey to determine the extent of implementation at the school level was also conducted. Findings show the breadth of challenges the program is facing emanating from conceptual to implementational. [...]
Keywords: 330; MTB-MLE; mother tongue; multilingual education; linguistically diverse contexts (LDCs); K-3; process evaluation; educational reform